2019
DOI: 10.1186/s13293-019-0262-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in PAR2-dependent regulation of primitive colonic cells

Abstract: Background Sexual dimorphism in biological responses is a critical knowledge for therapeutic proposals. However, gender differences in intestinal stem cell physiology have been poorly studied. Given the important role of the protease-activated receptor PAR 2 in the control of colon epithelial primitive cells and cell cycle genes, we have performed a sex-based comparison of its expression and of the effects of PAR 2 activation or knockout on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…Importantly, as for hematopoietic stem cells, a sexual dimorphism in PAR 2 -dependent GSK3β activation in colon stem cells has been observed [ 47 ]. The PAR 2 /GSK3β pathway has been triggered in colon progenitors from male mice, whereas females have displayed a PAR 2 /AKT pathway.…”
Section: Gsk3β In the Colon Crypt: Role And Controls By Proteases mentioning
confidence: 99%
“…Importantly, as for hematopoietic stem cells, a sexual dimorphism in PAR 2 -dependent GSK3β activation in colon stem cells has been observed [ 47 ]. The PAR 2 /GSK3β pathway has been triggered in colon progenitors from male mice, whereas females have displayed a PAR 2 /AKT pathway.…”
Section: Gsk3β In the Colon Crypt: Role And Controls By Proteases mentioning
confidence: 99%
“…All pharmacological tools were added to the colonoids every 2 days from D0 of the culture. Note that our previous ( 9 , 21 ) or preliminary experiments have shown that the control peptide with reversed sequence of SLIGRL and final concentration of DMSO (1 × 10 −4 %) did not modify colonoid growth/survival.…”
Section: Methodsmentioning
confidence: 77%
“…Due to the roles of PAR2 and GSK3β in the control of proliferation and differentiation of colon primitive cells ( 9 , 21 , 25 ), we have investigated the gene expression of a panel of factors implicated in these functions and potentially linked to a PAR2-dependent regulation. Under PS (Stress), the expression of Muc2 and Chga (but not Ngn3 and Dclk1 ) was downregulated, arguing in favor of a reinforcement of the GSK3β-dependent anti-secretory pathway ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR2 expression was higher in db/db compared to that in db + mice. PAR2 controls and activates critical negative signaling molecule gene expressions involved in primitive cell proliferation [ 42 ]. In addition, PAR2 signaling activation exerts a pivotal role in hepatic insulin resistance that subsequently leads to systemic steatosis in obesity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%